Original Article-Correlation and Comparison of Cheiloscopy, Dactyloscopy and Palatoscopy with Blood Groups among Dental Students From Western Maharashtra - Srigiri Surath1, Sushma Bommanavar2, Sudha B Mattigatti3, Uzma Belgaumi4, Vidya Kadashetti2, Wasim K (Indian Journal of Forensic Medicine & Toxicology, 2020)
Personal identification is of paramount importance in the forensic odontology for ethical, humanitarian and criminal investigations. In forensic odontology, scientific methods using DNA is considered to be the gold standard method of identification; however, it’s expensive and time-consuming approach have circumvented the need for less expensive and faster methods of identification. The latest inexpensive approach of quantifying evidences for identification of suspect in crime is using lip print, fingerprint, palatal rugae & blood grouping and this has gained tremendous importance in the present days. Hence, the aim of the present study is to correlate and compare Cheiloscopy, Dactyloscopy and Palatoscopy with blood group and Rh factor. Method: A total of 200 dental students between the age group18 to 25 years were included in the study. Lip print, finger print and palatal rugae patterns with ABO blood groups were collected and compared using Chi square test. The data was analysed using SPSS version 10.0 statistical package. Results & Conclusion: Statistically significant correlation existed between lip print and ABO-Rh factors (?2statistic = 37.56, p value <0.05) and between finger prints and ABO-Rh factors (?2 statistic = 30.6, p value < 0.05). No association was found between palatal rugae with ABO-Rhesus blood groups (?2 statistic = 17.71, p value >0.05).